2022
DOI: 10.1002/adfm.202208539
|View full text |Cite
|
Sign up to set email alerts
|

Extended Near‐Infrared Photovoltaic Responses of Perovskite Solar Cells by p‐Type Phthalocyanine Derivative

Abstract: The absent photo‐response in near‐infrared (NIR) light (>800 nm) of lead‐based perovskite solar cells (PSCs) limits the further improvement of their power conversion efficiency (PCE). Here, a narrow bandgap p‐type phthalocyanine derivative (Copper(II) 2,3,9,10,16,17,23,24‐octakis((4‐(bis(4‐methoxyphenyl)amino)phenyl)ethynyl)phthalocyanine –8TPAEPC) with NIR absorption is synthesized to extend the photovoltaic response of perovskite to 850 nm. After doping the 8TPAEPC into the perovskite photoactive layer, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The photovoltaic properties of some selected perovskite devices using Pc compounds as additives in the perovskite layer are summarized in Table 4. 139–147…”
Section: Application Of Phthalocyanines In Pscsmentioning
confidence: 99%
See 2 more Smart Citations
“…The photovoltaic properties of some selected perovskite devices using Pc compounds as additives in the perovskite layer are summarized in Table 4. 139–147…”
Section: Application Of Phthalocyanines In Pscsmentioning
confidence: 99%
“…8TPAEPC ( 74 ), a CuPc compound with eight triphenylamine groups grafted into the peripheral side of Pc, was used as the dopant for a mixed-ion perovskite film and enhanced the PCE of the perovskite devices from 20% to 22.10%. 147 As a narrow band gap additive, 8TPAEPC could extend the NIR photo-response of the perovskite film from 760 to 850 nm, which consequently enhanced the J SC value of the device from 22.8 to 24 mA cm −2 . It was indicated that there are electrostatic interactions between 8TPAEPC and perovskite molecules, which assisted the crystal growth of the perovskite, leading to more packed crystal grains and smoother surface in the final film.…”
Section: Application Of Phthalocyanines In Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…8TPAEPC was also applied as dopant-free HTM yielding 20.42% PCE and showing that also provides good moisture stability. 74…”
Section: Phthalocyanines In Perovskite Solar Cellsmentioning
confidence: 99%
“…[27][28][29][30][31] Besides the optimization of the central building block, the peripheral donor groups also play crucial roles in determining the properties and photovoltaic performance of corresponding HTMs. [32][33][34][35][36][37][38][39] However, the effects of the planarity of the core building block together with the peripheral donor groups on the photovoltaic performance of HTMs haven't been compared in detail. Revealing the impact of the planarity of the core building block and peripheral donor groups on the material properties will be favorable for better developing highly efficient HTMs.…”
Section: Introductionmentioning
confidence: 99%